Key mortality factors affecting populations of the honeybee Apis Mellifera (L.) in Panabo, Davao del Norte - Soriano, Nezer A. (2000)
This study aims to determine the physical and biological factors that affect the mortality of A. mellifera in artificial beehives over six generations during the January-May period. This was done by constructing a life table of the honeybee population and plotting as mortality curve. The data were then statistically tested using ANOVA, regression and correlation analyses. The results showed no significant change in mortality over time. Mortality was not affected by temperature, rainfall and cloud cover. The biological factors that influenced mortality include desiccation, foulbrood and mite attacks. Since mortality was highest during the egg stage, it is recommended that egg density be increased to achieve a high population